Draft genome sequence of sulfur-reducing archaeon Thermococcus thioreducens DSM 14981T - Hong,Sung-Jun (2017)
Abstract Thermococcus thioreducens DSM 14981T, a sulfur-reducing archaeon, was isolated from the rainbow hydrothermal vent site on the Mid-Atlantic Ridge. Herein, we report the draft genome sequence of T. thioreducens DSM 14981T; we obtained 41 contigs with a genome size of 2,052,483 bp and G + C content of 53.5%. This genome sequence will not only help understand how the archaeon adapts to the deep-sea hydrothermal environment but also aid the development of enzymes that are highly stable under extreme conditions for industrial applications.